French grammar drills - Kurbegov, Eliane (New York McGraw-Hill, 2023)
When it comes to learning grammar, the best way is to Just Do It! For learning grammar, you'll find the most success in retaining your skills through drills, drills, and more drills. French Grammar Drills reinforces your knowledge and enhance your ability to read, write, and speak in French. This book introduces essential grammar concepts, with practical examples to demonstrate their correct usage. You will flex your grammar muscle with the exercises included in each section. Inside this new edition you'll find: more than 200 exercises accompanied by an answer key; authentic examples to show you correct grammar usage; and, new review sections that will bring you up to speed on grammar."--Publisher's description.
Part 1. Articles and adjectives -- Part 2. Plurals, quantity, and partitive articles -- Part 3. Adjectives -- Part 4. Adverbs -- Part 5. Subject, stressed, and object pronouns -- Part 6. Possessive, demonstrative, and interrogative pronouns -- Part 7. Relative pronouns -- Part 8. Prepositions and conjunctions -- Part 9. Basic verbal structures -- Part 10. Other verbal structures -- Review 10
"Audio recordings, interactive quizzes, and flashcards are available to support your study of this book. Go to www.mhlanguagelab.com to access the online version of this application or to locate links to the mobile app for IOS and Android devices. Alternatively search "McGraw Hill Language Lab" in the iTunes app store or Google Play store". -- Title page verso
Keywords: French language -- Textbooks for foreign speakers -- English; French language -- Grammar -- Problems, exercises, etc; French language -- Self-instruction.